Mathematics Standard level for the IB Diploma - Smedley, Robert; Wiseman, Garry (Oxford : Oxford University Press, 2004)
Matching the Mathematics Standard Level course of the International Baccalaureate Diploma Programme, this book is adapted in consultation with senior examiners to ensure the coverage of the syllabus.
Keywords: Matematik; Mathematics; Mathématiqu